PREPARATION AND VALIDATION OF AN AURICULAR ACUPUNCTURE POINT PROTOCOL FOR HEADACHES - Andrade, Kaue Batista; Rodrigues, Carolina Amaral Oliveira; Souza, Vitória Cristina Ferreira; Teixeira, Wesley Silva; Gusmão, Ricardo Otávio Maia; Moura, Caroline de Castro; Araújo, Diego Dias de (Cogitare Enfermagem, 2024)
Objective: To develop and validate the content of an auricular acupuncture point protocol for the treatment of headaches. Method: A methodological study, carried out in June 2023 in Montes Claros, Minas Gerais, Brazil. It was structured in three stages: Planning (bibliographic survey and identification of the study variables); Construction of the instruments (characterization of the experts, point protocol and treatment regime); and Content validation in charge of 15 experts. In the data analysis, an absolute agreement percentage equal to or greater than 80% was used. Results: The auricular acupuncture protocol for the treatment of headaches that was validated by experts consisted of the following points: “Door of the Mind” (93.3%), Kidney (86.7%), Sympathetic (86.7%), Anxiety (86.7%), Subcortex (86.7%), Brainstem (86.7%), Frontal (86.7%), Occipital (86.7%), Temporal (86.7%) and Liver (80%). Conclusion: the auricular acupuncture protocol for the treatment of headaches was considered valid, which will allow its use in the clinical practice and research studies.